Efeitos do Hidróxido de Cálcio e da Clorexidina sobre a expressão de citocinas em infecções endodônticas - Warley Luciano Fonseca Tavares (2012)
Introduction: Root canal treatment typically involves cleaning and shaping procedures followed by treatment with antibacterial endodontic dressing between appointments and, ultimately, three-dimensional, hermetic filling. The use of calcium hydroxide is an effective step in killing bacteria that remain after cleaning and shaping procedures. It also induces hard tissue formation and is effective for stopping inflammatory exudates. Chlorhexidine (CHX) is effective as an irrigation solution and is utilized as an endodontic dressing. Objective: The aim of this study was to assay the influence of calcium hydroxide and CHX on periapical interstitial fluid from human root canals. Methods: The mRNA expression levels of the cytokines IFN-, TNF-, IL-1, IL- 17A, and IL-10 as well as the chemokine MCP-1 were assayed by real-time PCR, immediately after root canal cleaning and 15 days later. Results: Levels of IL-1, IFN-, IL-10, and the chemokine CCL2/MCP-1 were increased in teeth without endodontic dressings. However, with calcium hydroxide or CHX interappointment dressings, statistically significant changes were observed in cytokine mRNA expression. Conclusions: Analyses of cytokines and the chemokine CCL-2/MCP-1 demonstrated the benefits of calcium hydroxide and CHX as root canal dressings because it impedes the increase of all mediators during the experimental time.